2001
DOI: 10.1159/000050972
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Analysis in Immature Testicular Sperm Cells at Different Developmental Stages

Abstract: Testicular sperm extraction and intracytoplasmic sperm injection (TESE-ICSI) is a frequently used therapeutic option in azoospermic males. Genetic imprinting is a mechanism of gene regulation – mediated by the methylation of deoxyribonucleic acids (DNA) – by which only one of the parental copies of a gene is expressed. Whether the establishment of the genetic paternal imprint in this immature haploid sperm cell is complete and stable at this stage of maturation has never been analysed. In the present study, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…This is consistent with those studies that found that methylation patterns in relation to imprinted alleles are already defined at the spermatogonia stage (79,80).…”
Section: Intracytoplasmic Sperm Injectionsupporting
confidence: 93%
“…This is consistent with those studies that found that methylation patterns in relation to imprinted alleles are already defined at the spermatogonia stage (79,80).…”
Section: Intracytoplasmic Sperm Injectionsupporting
confidence: 93%
“…Spermatozoa isolated from micromanipulation were fewer and thus subjected to alkaline lysis (Manning et al, 2001). Bisulfite conversion was conducted with the EZ DNA Methylation-Gold Kit (Zymo Research, Orange County, CA, USA) according to the manufacturer's protocols.…”
Section: Dna Extraction and Bisulfite Conversionmentioning
confidence: 99%
“…This fact may explain the deviation between the results of HUMARA and SNRPN analysis (Table 2) and the very low percentage of positive results observed for HUMARA locus methylation in nonobstructive men with spermatozoa. The SNRPN analysis was informative about the stages of spermatogenesis before and after the pachytene spermatocytes evolved from the diploid cells, whereas HUMARA analysis was informative only for the pachytene spermatocytes when X-inactivation occurred (4,10). Therefore, SNRPN methylation analysis seems to confer different information than does HUMARA in terms of spermatogenesis and concordance with microscopy.…”
Section: Figurementioning
confidence: 94%
“…This outcome is probably due to the presence of the unmethylated paternal allele in almost all spermatogenic stages, including the round-spermatid stage (10). Germ cells of all preceding stages have not yet established the paternal imprint.…”
Section: Figurementioning
confidence: 99%